2006
DOI: 10.1021/cb600187q
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Chaperones and Permissive Temperatures Alter the Cellular Localization of Gaucher Disease Associated Glucocerebrosidase Variants

Abstract: Point mutations in the lysosomal hydrolase, glucocerebrosidase (GC), can cause Gaucher disease, a common lysosomal storage disease. Several clinically important GC mutations impede folding in the endoplasmic reticulum (ER) and target these enzymes for ER-associated degradation (ERAD). The removal of these misfolded proteins decreases the lysosomal concentration of GC, which results in glucosylceramide accumulation. The most common GC variant, N370S, and other clinically relevant variants, G202R and L444P, exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
156
0
6

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(179 citation statements)
references
References 52 publications
17
156
0
6
Order By: Relevance
“…Our results showing that the effect on imiglucerase and N370S GCase is comparable in magnitude to that observed using patient cells suggest that the major (but not necessarily the only) mechanism by which competitive inhibitors increase lysosomal levels of GCase is by reducing degradation within the lysosome rather than an effect on protein folding and trafficking. A reduction in lysosomal degradation in the presence of unaltered transport to the lysosome is consistent with many of the reports demonstrating an increased ratio of lysosomal to nonlysosomal protein levels in the presence of competitive inhibitors (18,21).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results showing that the effect on imiglucerase and N370S GCase is comparable in magnitude to that observed using patient cells suggest that the major (but not necessarily the only) mechanism by which competitive inhibitors increase lysosomal levels of GCase is by reducing degradation within the lysosome rather than an effect on protein folding and trafficking. A reduction in lysosomal degradation in the presence of unaltered transport to the lysosome is consistent with many of the reports demonstrating an increased ratio of lysosomal to nonlysosomal protein levels in the presence of competitive inhibitors (18,21).…”
Section: Discussionsupporting
confidence: 91%
“…To evaluate this possibility, we investigated the effect of the competitive inhibitor NN-DNJ on the intracellular stability of purified N370S and imiglucerase in macrophages. It is interesting that the 2-3-fold increase in GCase levels we observed after 24 h in the presence of NN-DNJ is comparable with the increase originally reported using Gaucher patient fibroblasts (20) as well as subsequent studies in patient fibroblasts using several different competitive inhibitors (17,21), suggesting that the mechanism(s) of action is similar in all cases. In our experiments, both proteins were already folded and targeted to lysosome via the mannose receptor, so an effect on protein folding or transport from the ER to lysosome could be ruled out in this case (36).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Some of the mutant GCase proteins are structurally unstable (Sawkar et al , 2006 ;Lieberman et al , 2007 ;Bendikov -Bar et al, 2011 ), and this may directly affect α -synuclein aggregation. In a study of brain samples from patients with PD and DLB, samples with a homozygous GBA1 mutation showed that > 80 % of the LBs were co-localized with GCase, and those with a heterozygous GBA1 mutation showed a 75 % GCase co-localization rate (range, 32 -90 % ) with LBs, compared to a mean of 4 % in patients with PD and DLB without a GBA1 mutation (Goker -Alpan et al, 2010 ).…”
Section: Gba1 Mutations and Lewy Body Pathologymentioning
confidence: 99%